2019
DOI: 10.1111/ajd.13090
|View full text |Cite
|
Sign up to set email alerts
|

Review of non‐invasive body contouring devices for fat reduction, skin tightening and muscle definition

Abstract: Non-invasive body contouring is a rapidly growing field in cosmetic dermatology. Non-invasive contouring devices improve the body's appearance through the removal of excess adipose tissue, particularly in areas in which fat persists despite optimal diet and exercise routine. The technology can also be used for skin tightening. This article reviews the five FDA-approved non-invasive body contouring modalities: cryolipolysis, laser, high-intensity focused electromagnetic field, radiofrequency and high-intensity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
102
0
10

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(113 citation statements)
references
References 35 publications
1
102
0
10
Order By: Relevance
“…Many treatments claim to reduce the abdominal fat deposits, tighten the skin, and improve skin texture and striae distensae. 17 The goal of noninvasive tissue tightening is to reverse these changes by rebuilding the collagen and elastic scaffold of the dermis. The common pathway for skin tightening is via the production of heat.…”
Section: Discussionmentioning
confidence: 99%
“…Many treatments claim to reduce the abdominal fat deposits, tighten the skin, and improve skin texture and striae distensae. 17 The goal of noninvasive tissue tightening is to reverse these changes by rebuilding the collagen and elastic scaffold of the dermis. The common pathway for skin tightening is via the production of heat.…”
Section: Discussionmentioning
confidence: 99%
“…Some other studies have shown that PBM can be used in body contouring. [18][19][20][21][22] Sadly, there is no standardisation of the protocol. The treatments vary in terms of the number of sessions , their frequency (1-3 times per week) and wavelength (532 nm, 635 nm, 660 nm, 1060 nm), while other dosimetry information, such as irradiance (W/cm 2 ) and radiant exposure (J/cm 2 ), are frequently not mentioned.…”
Section: Open Accessmentioning
confidence: 99%
“…The inclusion criteria will be: Sedentary women, aged between 18 and 40 years and with the presence of abdominal fat (thickness of adipose subcutaneous tissue of the abdominal wall) greater than 15mm (23) confirmed by adipometry, using as a reference point 2 cm from the right side of the umbilical scar (24) . The disclosure will be made by a digital pamphlet published on social networks and in printed form spread over Universidade Federal do Paraná (UFPR).…”
Section: Inclusion Criteriamentioning
confidence: 99%